Literasi Digital Pemanfaatan Modul Aplikasi Sevima Edlink dalam Perkuliahan Daring Mahasiswa Prodi Bimbingan dan Konseling FKIP Universitas PGRI Mahadewa Indonesia - Ni Komang Sri Yuliastini Yuliastini; Ni Made Dwi Narita Kusumawardani (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
This paper aims to describe digital literacy by utilizing the edlink application module in online lectures for Guidance and Counseling Study Program students, FKIP University, PGRI Mahadewa Indonesia. Utilization of technology is not new for students and in almost every activity can not be separated from technology products. Thus, the Guidance and Counseling Study Program lecturer must also be able to use or create information and technology-based learning media. Among the intermediaries or learning media is the edlink application module. With this media, lecturers can provide lecture materials that can be accessed by students and package their learning activities by utilizing the features available in Edlink and based on digital literacy. The use of edlink by lecturers provides students with experience in selecting and analyzing the information needed in online lecture activities. The stages contained in digital literacy include digital competence, digital use, and digital transformation. In general, this article will explain about the edlink application module, digital literacy, and online lectures through the digital literacy-based edlink application module.